2014
DOI: 10.1139/apnm-2013-0276
|View full text |Cite
|
Sign up to set email alerts
|

Mouth rinsing improves cycling endurance performance during Ramadan fasting in a hot humid environment

Abstract: This study examined the effect of mouth rinsing during endurance cycling in a hot humid environment (32 °C and 75% relative humidity) on athletes in the Ramadan fasted state. Nine trained adolescent male cyclists completed 3 trials that consisted of a carbohydrate mouth-rinse (CMR), a placebo mouth-rinse (PMR), and a no-rinse (NOR) trial during the last 2 weeks of Ramadan. Each trial consisted of a preloading cycle at 65% peak rate of oxygen consumption for 30 min followed by a 10-km time trial (TT10 km) under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 28 publications
4
33
0
Order By: Relevance
“…However, there were no differences between time trial performance and RPE when rinsing with CHO compared to the placebo (12.9 ± 1.7min vs. 12.6 ±1.7min; RPE 6 ± 2 vs. 7 ±2) (Muhamed et al 2014). …”
Section: Cho Mouth Rinse Dose Responsementioning
confidence: 79%
See 3 more Smart Citations
“…However, there were no differences between time trial performance and RPE when rinsing with CHO compared to the placebo (12.9 ± 1.7min vs. 12.6 ±1.7min; RPE 6 ± 2 vs. 7 ±2) (Muhamed et al 2014). …”
Section: Cho Mouth Rinse Dose Responsementioning
confidence: 79%
“…However, Ispolgou et al (2015) showed no statistical difference in performance during a 1h cycling time trial when rinsing with a 4%, 6%, or 8% CHO mouth rinse when participants had consumed a meal three hours prior to beginning the trial. Muhamed et al (2014) found that time trial performance improved with both a placebo and CHO mouth rinse compared to not rinsing when participants were fasted during Ramadan. Lastly, Ataide-Silva et al (2016) found that following a muscle glycogen depleting bout of exercise and subsequent overnight fast, CHO mouth rinse restored EMG activity of the vastus lateralis and Examining studies demonstrating performance improvements with a CHO mouth rinse shows the importance of prandial state on the effectiveness of using a CHO mouth rinse.…”
Section: Chapter Four: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Meanwhile, as the deprivation of fluid and food intake is increased, even exposure in the oral cavity appears to enhance performance in the heat (Che Muhamed, Mohamed, Ismail, Aziz, & Singh, 2014). Of course, the methodology used in these studies cannot rule out a placebo effect of fluid exposure or a nocebo effect of no treatment.…”
Section: Oral Intake Of Fluid and Sports Performancementioning
confidence: 99%